Strategies for patient empowerment through the promotion of medicines in Israel: regulatory framework for the pharmaceutical industry - Eyal Schwartzberg; Zohar Barnett-Itzhaki; Itamar Grotto; Eli Marom (BMC, 2017)
Abstract The correct and rational use of medications can have a positive direct impact on disease outcomes, as well on the utilization of the health system resources. Unfortunately, 50% of the patients do not take their medications as prescribed, largely due to lack of patients' understanding of their medical condition, as well as the lack of reliable medicine information. There are multiple strategies implemented in many countries to tackle this challenge including: disease awareness campaigns (DAC) to raise the public awareness to specific diseases, direct-to-consumer advertisement (DTCA) to raise the public awareness to prescription medicines, specific treatments and over-the-counter (OTC) products to improve the accessibility of patients to specific medicines. Prior to 2013, the Israeli policy prohibited prescribing medication advertising and prevented the flow of information from pharmaceutical companies to the patient. In the last five years, the Pharmaceutical division in the Israeli Ministry of Health, as part of the "empowering the patient" agenda, has taken new innovative approaches to raise public awareness to diseases, medications and appropriate usage, as well as promotion of information to improve patient adherence to the prescribed medication. This paper elaborates on the aforementioned strategies implemented in developed countries, and specifically focuses on newly implemented strategies and regulations in Israel regarding pre- and post-prescription information, to improve patient appropriate utilization and adherence to medication.